Unusual Oligomeric Laccase-like Oxidases from Ascomycete Curvularia geniculata VKM F-3561 Polymerizing Phenylpropanoids and Phenolic Compounds under Neutral Environmental Conditions - Zhanna V. Renfeld; Alexey M. Chernykh; Boris P. Baskunov; Anastasya S. Gaidina; Nina M. Myasoedova; Anna D. Egorova; Olga V. Moiseeva; Sophya Yu Gorina; Marina P. Kolomytseva (Microorganisms, 2023)
The unique oligomeric alkaliphilic laccase-like oxidases of the ascomycete C. geniculata VKM F-3561 (with molecular masses about 1035 and 870 kDa) were purified and characterized for the first time. The ability of the enzymes to oxidize phenylpropanoids and phenolic compounds under neutral environmental conditions with the formation of previously unknown di-, tri-, and tetrameric products of transformation was shown. The possibility to obtain industrially valuable compounds (dihydroxybenzyl alcohol and hydroxytyrosol) from caffeic acid using laccase-like oxidases of C. geniculata VKM F-3561 has been shown. Complete nucleotide sequence of the laccase gene, which is expressed at the peak of alkaliphilic laccase activity of the fungus, and its promoter region were determined. Based on the phylogenetic analysis of the nucleotide sequence, the nearest relationship of the isolated laccase gene with similar genes of fungi of the genera Alternaria, Bipolaris, and Cochliobolus was shown. Homologous model of the laccase structure was predicted and a proton channel was found, which was presumably responsible for the accumulation and transport of protons to T2/T3-copper center in the alkaliphilic laccase molecule and providing the functional activity of the enzyme in the neutral alkaline environment conditions.